Recent Progress in the Asymmetric Intermolecular Halogenation of Alkenes - Chen, Jie; Zhou, Ling (Synthesis, 2014)
As a long-standing problem in organic chemistry, and a very useful transformation in organic synthesis, the catalytic asymmetric halogenation of alkenes has only recently been reported. New catalysts and novel approaches have been developed for asymmetric halocyclizations. Although mechanism studies indicated the asymmetric intermolecular halogenation of alkenes is more difficult, important breakthroughs have also been achieved. In this review article, the scope, mechanism, and limitations of recently developed catalytic asymmetric intermolecular halogenation of alkenes are described.1 Introduction2 Asymmetric Intermolecular Halogenation of Alkenes2.1 Asymmetric Halogenation of α,β-Unsaturated Compounds2.2 Asymmetric Halogenation of Allylic Alcohols2.3 Asymmetric Halogenation of Enecarbamates and Enamides2.4 Asymmetric Halogenation of Allylic Sulfonamides2.5 Asymmetric Halogenation of Unfunctionalized Alkenes3 Summary and Outlook
Keywords: alkenes; asymmetric catalysis; enantioselectivity; electrophilic addition; halogenation